Could nutrition prevent the onset of dementia? Current evidence from epidemiological and intervention studies. (June 2012) - Barberger-Gateau, Pascale; Samieri, Cécilia; Allès, Benjamin; Féart, Catherine
SUMMARY  Cardiovascular and metabolic risk factors for cognitive decline and dementia, such as hypertension, diabetes, metabolic syndrome and obesity, may be modified by diet. Moreover, several classes of nutrients, including long-chain ω-3 polyunsaturated fatty acids, antioxidants (i.e., vitamins C and E, carotenoids and polyphenols) and vitamins B and D can lower inflammation and oxidative stress associated with neurodegeneration, in addition to specific neuroprotective effects. However, most randomized clinical trials of supplementation with high doses of single nutrients have been disappointing. Healthy dietary patterns, such as the Mediterranean diet, combine several classes of nutrients that could work in synergy to slow down cognitive decline. Healthy dietary habits at midlife could contribute to decrease the risk of late-life dementia.